Rancangan Timbangan Digital dengan Alat Dimensi Otomatis Menggunakan Metode Kano - Siswanto, Siswanto (SURYA TEKNIKA, 2025)
Supply Chain Management (SCM) is a department of material & service provision at JOB Pertamina – Medco E&P Tomori Sulawesi. Data from each material has been entered into (SAP) such as material type, weight and material dimension size. To find out the dimensions of the incoming material, manual measurements are still carried out. Redesigning the digital bench scale by adding the function of measuring the dimensions of goods so that they can be displayed automatically via a liquid crystal display (LCD). The Kano method classifies the attributes of the digital bench scale by adding the function of measuring the dimensions of goods. From the results of the research on the redesign of the digital bench scale, 5 trials of the designed tool, there was a difference in the distance between manual and automatic measurements of around 0.2-1.5 cm which was caused by the HC-SR04 ultrasonic sensor which was not precise.